All-Oral Low-Dose Chemotherapy TEPIP is Effective and Well-Tolerated in Relapsed/Refractory Patients With Aggressive B-Cell Lymphoma - Fante, Matthias A.; Felsenstein, Mona; Mayer, Stephanie; Gerken, Michael; Klinkhammer-Schalke, Monika; Herr, Wolfgang; Vogelhuber, Martin; Reichle, Albrecht; Heudobler, Daniel (Frontiers in Oncology, 2022)
Purpose: Treatment options in patients (pts.) with advanced relapsed and refractory aggressive B-cell lymphoma are limited. Palliative all-oral chemotherapy regimens reduce in-patient visits and contribute to quality of life. The all-oral low-dose chemotherapy regimen TEPIP comprises the conventional chemotherapy agents trofosfamide, etoposide, procarbazine, idarubicin and prednisolone. Methods: Safety and efficacy of TEPIP was evaluated in an observational retrospective, single-center study at the University Medical Center Regensburg between 2010 and 2020. Treatment with TEPIP was applied for 7 or 10 days during a 28-days period. In a subgroup of fit and therapy-motivated pts. rituximab was added. End points were overall survival (OS) and progression free survival (PFS). Adverse events ≥ CTCAE grade III were reported. Results: 35 highly pre-treated pts. with aggressive B-cell lymphoma were enrolled. Median age at TEPIP start was 67 years and 85 % of pts. received TEPIP as ≥ third treatment line. Overall response rate (ORR) was 23 % (CR 17 %). Pts. benefited from additional rituximab administration (ORR 67 %) and a lower number of pre-treatments (ORR 41 %). The OS was 3.3 months (m) with a 1y-OS of 25.7 % and the PFS amounted to 1.3 m with a 1y-PFS of 8.8 %. OS and PFS were significantly prolonged in pts. that responded to treatment or additionally received rituximab. Adverse events were mainly hematological and occurred in 49 % of pts. Conclusion: TEPIP was well-tolerated and induced respectable response in a difficult-to-treat patient cohort. In particular, the all-oral administration enables out-patient use with palliative intent.